Theory and Practice of Dry Beneficiation Technology in China - Q. R. Chen (International Mineral Processing Congress, 2014)
Wet processes are commonly used in coal preparation field home and abroad. Dry coal cleaning technology is very necessary in China because more than 2/3 of coal resources deposited in arid areas, which are difficult to separate coal with wet processes. A particular interest of this article is the discussion of separation research development of dry coal cleaning in China, such as an air dense medium fluidized bed (ADMFB) beneficiation technology, a compound dry (pneumatic) separation technology and a triboelectrostatic separation technology. The fundament and importance of dry coal cleaning methods above were introduced. On the basis of analyzing parameters which influence the performance of separators, including that of structure, technologic and operating, the separation research status of dry coal cleaning methods, especially the ADMFB beneficiation technology, were discussed and reviewed. The recent developments, especially the fluidized bed beneficiation for <6mm fine coal with an external energy assisted, including a vibrated fluidized bed and a magnetically fluidized bed, and the triboelectrostatic separation for <1mm fine coal are also introduced. The study and application results in China show that dry coal cleaning technologies can efficiently beneficiate different coals with different sizes. The ADMFB can separate >6mm coarse coal with an E value of 0.05~0.08, the external energy assisted fluidized bed can separate <6mm fine coal with an E value of 0.07~0.09, the triboelectrostatic technology can efficiently separate <1mm fine coal, and the compound dry separation technology can efficiently separate >3mm coal with a easy washability. The dry coal cleaning provides an efficient and lower cost clean approach for coals distributed in arid areas.